Ocular Penetration Trauma due to Bamboo Resulting in Evisceration: A Case Report: Poster Presentation - Case Report - General practitioner - Indah Latifah; dr. Lailus Sofatul Layyin, Sp. M (Majalah Oftalmologi Indonesia, 2023)
Introduction : Penetrating ocular trauma includes open-eye trauma, which leads to the time and a precision of eye- penetrating trauma’s management determine the advanced vision prognosis. In this case a male experience penetration trauma of the right eye due to exposure to the bamboo, delaying and inadequate management resulted in evisceration of the right eye. A 42-year-old male came to ER RSUD Prof. Soekandar mojokerto with bloody right eye and pain from getting a piece of bamboo from two days before entering the hospital. The patient also complained that the right eye is swollen so that it is unable to open the eyes. vision examination revealed LP (-) in the right eye, visual acuity in the left eye was 6/6, soft palpation in the right eye, normal palpation in the left eye, examination of the right anterior segment of the eye revealed that part of the eyeball content had prolapsed and for the left eye within the normal range. During laboratory tests, 15.280 white blood cells were found, which confirmed the infection of the right eye. Case Illustration : Descriptive Study Discussion : The observations on these patients include covered the right eye, antibiotic, steroids, and analgesic by intravenous injection. Based on the condition of the patient's right eye, it is advisable to do evisceration of the right eyeball under general anesthesia. Conclusion : Penetrating ocular trauma resulting in extensive intra ocular tissue damage and poor vision prognosis, considered for evisceration, in order to prevent the development of the sympatetic ophthalmia.